Unraveling cerebroprotective potential of fenchone: A combined in vivo and in silico exploration of nitric oxide synthase modulation - Bangaru Mamatha; Anka Rao Areti; DSNBK Prasanth; Narender Malothu (Brazilian Journal of Pharmaceutical Sciences)
Abstract In this study, we investigated the cerebroprotective effects of fenchone (FEN) against brain ischemia through in silico and in vivo approaches, focusing on the inhibition of nitric oxide synthase (NOS) and the modulation of oxidative stress markers. Molecular docking revealed the potential binding affinity of FEN for the NOS active site, with a binding energy of -6.6 kcal/mol. This was validated through molecular dynamics simulations over a 100 ns time frame, demonstrating stability and favorable interaction profiles. Wistar albino rats underwent bilateral common carotid artery occlusion/reperfusion (BCCAO/R) followed by FEN administration at doses of 100 and 200 mg/kg. Our results indicated a significant reduction in cerebral infarction size and improvements in electroencephalography (EEG) signal magnitude with FEN treatment. Additionally, FEN restored the activity of antioxidant enzymes (catalase and superoxide dismutase) and decreased malondialdehyde (MDA) and nitric oxide (NO) levels and infarct size compared to those in untreated ischemic rats. Histological analysis further corroborated the neuroprotective effects of FEN, demonstrating the structural preservation of neurons in the hippocampal CA1 region. Overall, the results suggest that FEN plays a neuroprotective role in brain ischemia, potentially through the inhibition of NOS, reduction of oxidative stress, and modulation of antioxidants, highlighting the potential of FEN as a therapeutic candidate for ischemic stroke management.